An Investigation of TFRC Over MANET Routing Protocol - Mohamad Rizal, Abdul Rejab (2010)
A Mobile Ad Hoc Network or MANET is a collection of wireless nodes that are able to junction standalone and which cannot be predicted by a temporary network without any fixed backbone infrastructure. Mobility and the non-fixed infrastructure of MANET are also attractive for sensor networks applications, rescue operations, military, and time-critical applications. MANET routing protocol consist of a table driven and on-demand routing protocol and the specific focus to on-demand routing protocol such as Dynamic Source Routing (DSR) and Ad Hoc On-Demand Distance Vector (AODV). The TCP-Friendly Rate Control (TFRC) provides a smoother congestion control, smoother throughput variance compared with Transmission Control Protocol (TCP). In this paper, we propose an investigation of the performance metrics such as jitter, packet delay, and throughput. We compare the performance metrics of DSR and AODV using extensive simulation experiments Network Simulation (ns-2). Based on the research results, DSR operates better in TFRC over AODV routing protocol and it performed with better in jitter, throughput and packet delay. The DSR protocol perform better with 19.45% to 23.27% less jitter, 36.43% to 69.65% better throughput and 92.56% to 98.05% lower packet delay than the AODV protocol.